Review of the Implementation of the Bologna Process in Croatian Higher Education - Polić-Bobić, Mirjana (Array, 2006)
The legal framework in which the Bologna reform is being introduced in Croatia has been exposed, as well as the actions taken by the Ministry of education and the universities after Croatia signed the Bologna declaration.